Comparison of Stock Market Reactions to the 2024 Elections: Event Study Analysis of the IDX Sectoral Index - Sekar Sabina Larasati; Ade Widiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the capital market reaction at the sectoral level to the 2024 General Election in Indonesia, with the aim of providing deeper insight into how political events influence different industries. Using an event study methodology, the analysis is conducted over a 10-trading-day window surrounding February 14, 2024—the official election date—covering five days before and after the event. The research focuses on six major sectoral indices listed on the Indonesia Stock Exchange (IDX), namely Energy, Consumer Cyclicals, Financials, Basic Materials, Industrials, and Technology.Market reaction is measured through two primary dimensions: (1) changes in price valuation, represented by abnormal returns (AR), and (2) shifts in investor activity, measured through Trading Volume Activity (TVA), operationalized as the turnover ratio. Abnormal returns capture the extent to which price changes deviate from expected normal performance, while TVA reflects the level of investor engagement in each sector during the event window.To evaluate differences in market reaction across sectors, the Kruskal–Wallis test is applied for abnormal returns due to non-normal data distribution, and Welch’s ANOVA is used for TVA to account for heterogeneity of variances. The results reveal no statistically significant differences in abnormal returns across the six sectors, suggesting that price adjustments to election-related information occur uniformly across the market, reflecting a degree of informational efficiency. However, the analysis of TVA shows a highly significant difference among sectors. A Games–Howell post-hoc test further indicates that the Energy and Consumer Cyclicals sectors experienced notably higher trading activity compared to other sectors, especially the Financials sector, which recorded the lowest investor engagement.